Evaluating Factors Affecting the Adoption of a Mobile Assisted Business Application Using the Technology Acceptance Model - Awaluddin, Muhammad (Economic and Business Horizon, 2023)
Digital transformation requires organizations to ensure that employees adopt and effectively use new systems. Understanding the drivers of adoption is therefore essential, particularly in enterprise contexts where system utilization affects performance outcomes. This study examines the factors influencing the adoption of a mobile-assisted business application using the technology acceptance model. The model focuses on the relationships among perceived usefulness, perceived ease of use, attitude toward using, behavioral intention, and actual use. A two-phase approach was applied. First, a survey of internal users yielded 212 valid responses, analyzed with Covariance-Based Structural Equation Modeling. Second, system log data were collected to capture actual usage behavior. The findings show that perceived ease of use significantly affects PU (β = 0.58, p < 0.01), while both perceived usefulness and perceived ease of use positively influence attitude toward using (β = 0.41; β = 0.29, p < 0.01). Attitude toward using predicts behavioral intention (β = 0.52, p < 0.01), which subsequently drives actual use (β = 0.36, p < 0.01). Although model fit indices are satisfactory, the R² for actual use (13%) suggests additional contextual factors shape actual usage. this study extends TAM by integrating behavioral data and offers practical insights for enhancing adoption through usability improvements, user training, and performance-based incentives.